Holesterolni embolizmi - Fister, Miša (Medicinski razgledi, 2009)
Cholesterol embolism is a dinical syndrome in which cholesterol crystals breakfrom an atheromato us plaque in a larger artery and ocdude the lumen of small peripheral arteries. It commonly occurs after vascular intervention procedures, but can also occur spontaneously. Because of possible involvement of any organ system, the syndrome represents a diagnostic challenge.In dinicalpresentation, the most commonly involved organs are the skin (in the form ofblue toe syndrome or livedo reticularis) and kidneys (acute kidney failure), and there mayaIso be abdominal pain. Patients are usually older and have generalized atherosderosis, with or without its well-known manifestations. The diagnosis is more easily made when an embolism occurs acutely rather than when they are chronic. The diagnosis can be confirmed onlyby biopsy of the affected area that shows cholesterol crystals in the lumen of small arteries.Mortality from cholesterol embolisms is high, and their treatment is only symptomatic, aimed at slowing the progress of atherosderosis.
Keywords: Embolija holesterolna; Embolism, Cholesterol; ateroskleroza; Atherosclerosis; embolija; klinična slika; therapy; zdravljenje